2001
DOI: 10.1016/s0370-2693(01)01130-3
|View full text |Cite
|
Sign up to set email alerts
|

Heavy-quark colorimetry of QCD matter

Abstract: We consider propagation of heavy quarks in QCD matter. Because of large quark mass, the radiative quark energy loss appears to be qualitatively different from that of light quarks at all energies of practical importance. Finite quark mass effects lead to an in-medium enhancement of the heavy-to-light D/π ratio at moderately large (5-10 GeV) transverse momenta. For hot QCD matter a large enhancement is expected, whose magnitude and shape are exponentially sensitive to the density of colour charges in the medium. Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
918
10
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 900 publications
(965 citation statements)
references
References 21 publications
31
918
10
6
Order By: Relevance
“…We showed that the Ter-Mikayelian effect on the induced energy loss is comparable but somewhat larger than in [29]. In addition, it was shown shown that the induced contribution increases approximately linearly with L, as first reported in [33].…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…We showed that the Ter-Mikayelian effect on the induced energy loss is comparable but somewhat larger than in [29]. In addition, it was shown shown that the induced contribution increases approximately linearly with L, as first reported in [33].…”
Section: Discussionsupporting
confidence: 79%
“…Since finite parton masses shield collinear k → 0 singularity [33], our numerical computations are performed with zero momentum cutoff. We see that for heavy quarks, in the energy range E ∼ 5−15 GeV, the Ter-Mikayelian effect reduces the induced energy loss in this extension of the GLV approach somewhat more than in the BDMS approximation [29]. However, on an absolute scale, this only corresponds to a change of δ(∆E (1) /E) < 0.05, which is negligible.…”
Section: Heavy Quark Energy Loss At Rhicmentioning
confidence: 78%
See 2 more Smart Citations
“…Quarks are expected to lose less energy than gluons as a consequence of their smaller colour factor. In addition, the so-called "dead-cone effect" is expected to reduce small-angle gluon radiation of heavy quarks when compared to both gluons and light quarks [3][4][5]. Energy loss can be studied using the nuclear modification factor (R AA ), defined as the ratio of the PbPb yield to the pp crosssection scaled by the nuclear overlap function [6].…”
mentioning
confidence: 99%